Perbedaan Penurunan Berat Badan Berdasarkan Ketaatan Pelaku Diet Kombinasi Makanan Serasi (Food Combining) di Komunitas Qita Sehat Dengan Fc di Kota Semarang - Lutfi Chaenurisah; Agustin Syamsianah; Yuliana Noor S.U (Jurnal Gizi, 2016)
There are many versions of the diet to reduce the body weight in Indonesia. One of the diet is food combining (FC). Food Combining is setting a diet tailored to the needs of the body,related the time in the morning, noon and night. The devide of the time are called sirkandian so there are morning sirkandian, noon sirkandian and night sirkandian.The diet that;s refers to abalanced diet in order to get the best results for the purpose of health and other objectives. The specific characteriristics of FC is to be achieved by not mixing the acid food and the alkaliedfood, to be consumed together. Likes another diets, adherence to the rule of FC will be the key of successful in the diet.The aims of this study ia to know the difference of the body weight decline by an adherence of food combining dieters.This study is a analytical study with survey method and cross sectional aprroach. The sample of study is all members of Qita Sehat Dengan FCassociation, amount to 25 people.All of them are FC dieters. The deferent of body weight decline by an adherence of FC dieters were analyzed by Independent t-test.The results showed that generally an adherence of FC dieters are not good, so there are 40 % at morning sirkandian, 56 % at noon sirkandian and 40 % at night sirkandian. In 2 montof the study, the average of body wight dicline of the FC doeters is 3,72 kg. Generally, the body mass index (BMI) of the FC dieters are at normal category. There are many differences in body weight decline that significantly by p < 0.05 between the FC dieters who adherence with who not adherence of the other. There are not differences in BMI significantly by p > 0.05 between the FC dietwrs who adherence with whonot adherence of the others.There is a significantly difference in body weight decline by an adherence of FC dieters.There is not significantly difference in BMI by an adherence of FC dieters.Keywords: Food Combining, body weight decline, obedience, IMT